Manfaat Program Kerja Pkk Dalam Memperkuat Ketahanan Pangan Keluarga: Sebuah Analisis Berbasis Tiga Pilar Ketahanan Pangan dan Modal Sosial - Janeska Widia (PT PUSTAKA CENDEKIA GROUP, 2024)
Food security is a strategic priority in Indonesia's national development, requiring effective interventions down to the household level. The Family Empowerment and Welfare Movement (PKK), a community organization rooted throughout the country, plays a central role in this effort, although its contribution has often not been systematically analyzed. This article aims to analyze the benefits of PKK work programs in strengthening family food security using a comprehensive literature synthesis approach. The analytical framework is based on the three pillars of food security as mandated by Law Number 18 of 2012—food availability, accessibility, and utilization—and is enriched with the lens of social capital theory. The analysis shows that PKK flagship programs, such as the Beautiful, Organized, Beautiful, and Comfortable Yard (HATINYA PKK) and the Family Income Improvement Effort (UP2K), directly contribute to these three pillars. HATINYA PKK increases food availability by optimizing yard space, UP2K strengthens food accessibility by increasing family income, and nutrition education programs and active participation in Integrated Service Posts (Posyandu) increase food utilization to improve nutritional status and prevent stunting. The main thesis of this article is that the effectiveness and sustainability of these programs are underpinned by the PKK's fundamental function as a social capital-building engine. Through its hierarchical organizational structure and participatory activities, the PKK systematically cultivates networks, trust, and norms that serve as the foundation for community resilience and food self-sufficiency.